How is Mediation Integrated into the Dispute Resolution System of Civil Cases in Hungary? - Harsági, Viktória (Review of European and Comparative Law, 2023)
The article deals with the integration of mediation into the Hungarian justice system, with particular attention to its historical aspects, the connection between litigation and mediation and the conditions for becoming a mediator, as well as the two types of mediation.